(untitled) (diségno, 2022)
The paper aims to highlight the connection between organic geometry, proportional ratios and the conformation of musical instru- ments: emblematic examples of a folk design that spontaneously combines art and technique, innovation and tradition, listening and vision. It is a process of analysis that, through direct survey, structure-from-motion techniques, three-dimensional modeling, and the study of geometries, aims to document ethnic shapes and traditions: traces that, over the centuries, have triggered processes of innovation based on experimentation ‘poor’ in material but rich in creativity.